Efecto de la temperatura de austenización y revenido en la resistencia al desgate del acero SAE-1080 fabricado por SIDERPERU - Chávez Ruiz, Ricardo Arturo (2023)
In the present work, the wear behavior of high carbon steel bars (SAE-1080) _x000D_ manufactured by the SIDERPERU Company is studied. The type of wear studied is _x000D_ impact and abrasive, since these bars are used in the VOLCA mine in the mineral _x000D_ grinding process. The test tubes are cylindrical bars provided by SIDERPERU, _x000D_ which are 370 mm long and 38 mm in diameter. For this study, a bar mill was _x000D_ designed and built in the Materials Physics Laboratory to grind the mineral made up _x000D_ of sulfide and quartz for 3 hours and analyze the wear of the bars by means of the _x000D_ loss of mass of the bars. 8 test tubes divided into 2 groups were used, with 4 test _x000D_ tubes for each group. The specimens of the first group were austenitized at different _x000D_ temperatures: 790°C, 825°C and 875°C, and subjected to oil quenching treatment _x000D_ and then tempered at 450°C; the specimens of the second group were all _x000D_ austenitized at 790°C, quenched and then tempered at temperatures of 300°C, _x000D_ 450°C and 550°C. Tensile strength tests, hardness tests and metallographic _x000D_ analysis were performed. The results show that the bars in the as-supplied state _x000D_ present greater resistance to wear compared to the bars treated at austenitizing and _x000D_ tempering temperatures mentioned above. This indicates that the SAE 1080 bars _x000D_ manufactured by SIDERPERU have been manufactured efficiently and would _x000D_ guarantee their use for mineral grinding